(untitled) (Health Education in Practice: Journal of Research for Professional Learning, 2019)
Introduction: the case for change There are increasing mental health issues among young people, including higher education students. Millennial students face unique challenges with attention, critical thinking and managing stress. In addition, allied health students engage in multiple placements where they need to interact with real people in real time whilst being evaluated in assessment and treatment strategies. Some universities have been using wellness programs and mindfulness strategies to support student mental health across campuses for some time. However, as allied health students face unique challenges, there is a need for a particular focus on wellness at an individual allied health course level. The curriculum in allied health courses is determined by accreditation bodies and is comprehensive with little space for additional information. It is possible for short activities to be embedded in tutorials and the authors argue a focus on wellness is vital for the future allied health workforce. Methodology for pilot project This project used questionnaires to investigate student perceptions of a short program of activities to promote wellness and mindfulness in third year speech pathology students who were also engaging in clinical placements. Results and discussion Students were positive about the activities, developed their own wellness plan and learnt new strategies to manage their mental health at university and in their future careers. Future directions This short program could easily be adapted in other allied health courses.